Organizational Citizenship Behavior (OCB) Based on Leadership Style and Organizational Culture with Organizational Commitment as an Intervening Variable - Gemina, Dwi; Yuningsih, Erni; Putri, Adistiasari Kencana (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Organizational Citizenship Behavior (OCB) plays an important role in enhancing company effectiveness, with employees working to their fullest potential, greatly benefiting the company. This study aims to identify and analyze the direct and indirect effects of leadership style and organizational culture on OCB through organizational commitment as an intervening variable. The population in this study consists of 52 employees. Sampling was conducted using a saturation sampling method with a total sample of 52 employees. The data used in this study is ordinal data, which was converted into metric interval-scale data using the Method of Successive Interval (MSI). Data analysis includes descriptive and verificative methods, as well as Path Analysis and the Sobel Test for the intervening variable. The results show a direct and positive effect of leadership style on organizational commitment, organizational culture on organizational commitment, leadership style on OCB, organizational culture on OCB, and organizational commitment on OCB. Additionally, there is an indirect and positive effect of leadership style on OCB through organizational commitment, and organizational culture on OCB through organizational commitment